The Influence of Financial Literacy and Financial Management on the Financial Performance of MSMEs - Meldianus J Nabas; Aminah Aminah; Fausiah Fausiah; Azwin Hariyanto Cinta; Andi Novita Paramitha (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the influence of financial literacy and financial management on the financial performance of Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a strategic role in the national economy, but still face various financial management challenges that affect their low business performance. The research method used is a quantitative approach with survey techniques. Data was collected through questionnaires distributed to MSME actors and analyzed using multiple linear regression. The study finds that financial literacy has a positive and significant effect on the financial performance of MSMEs. In addition, financial management has been shown to have a positive, significant effect on financial performance. Simultaneously, financial literacy and financial management have a significant effect on the financial performance of MSMEs. These findings indicate that improving understanding and adopting good financial management practices are essential to enhancing MSME performance in a sustainable manner